"One Good Idea": A Physical Education Teacher Education Project Advocating for LGBTQ + Students in School Physical Education. Issue 1 (2nd January 2023) - Scanlon, Dylan; Walsh, Claire; Moody, Brigitte; Loughnane, Matthew; Kelly, Padraig; McManus, Martin; Browne, Daniel
Abstract: This article is co-written by teacher educators and pre-service teachers, and shares practical examples of how to design and enact a 'One Good Idea' project titled: 'How We Can All Be Allies'. This project allowed pre-service teachers the space to engage with and explore social justice issues, enhance advocacy skills, and to 'think outside the box' in supporting marginalized school students.